Suscipere digneris : Et fund og nogle hypoteser om Københavnerpsalteret Thott 143 2º og dets historie - Petersen, Erik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Erik Petersen: Suscipere digneris. A find and some hypotheses on the Copenhagen Psalter Thott 143 2° and its history.   The Copenhagen Psalter Thott 143 2º has often, and rightly, been praised as an outstanding example of the subtlety and artistic quality of Romanesque art in manuscripts. Its illumination, the saints of its calendar and litany place it in an English context. Two added elements, an obituary notice on the death in 1272 of Eric duke of Jutland, son of the Danish king Abel, and a prayer of an anonymous woman, link the codex to Medieval Denmark and Scandinavia as well. Addressing the Holy Trinity with the words Suscipere digneris the woman prays for herself, pro me misera peccatrice, and for the souls of her father and mother, of her brothers and sisters, of all members of her family, and for the souls of all brothers and sisters and familiares of her order. She also prays pro anima Byrgeri ducis. The occurrence of duke Birger, or Birger Jarl, in her prayer has given the book the name “Psalter of the Folkungar”, in particular in Scandinavian scholarship. The assumptions have been that the Psalter belonged to the Swedish aristocratic family of the Folkungar, that the duke Birger mentioned in the prayer was the older member of the family bearing that name (d. 1202), and that the book later passed to Mechtilde, the mother of duke Eric and widow of king Abel killed in 1252, who married the younger duke Birger in 1261. Duke Birger died in 1266, Mechtilde in 1288.   The fate of the Psalter from the end of the 13th century until it entered the huge library of count Otto Thott (1703–1785) has been entirely unknown. There are, however, a couple of clues to its history, one in the codex itself and one external, which do cast some light on its whereabouts. The first is a small piece of paper with bibliographical notes from the 18th century inserted at the very end of the codex. The second is an elaborate copy of the calendar and the prayer that I became aware of while working on the German humanist and theologian Johann Albert Fabricius (1668–1736) and his manuscripts. It could be proved that the copy was made in Fabricius’ own hand between 1720 and 1736. Since I knew that Fabricius did not leave Hamburg at any time during these years, it could also be proved that the Copenhagen Psalter must have been present in the city at least for some time in the same period. The codex did not belong to Fabricius, and since he left no information about it apart from the copy itself, I was not able to determine how he had had access to it.   The answer was to be found in a hitherto unnoticed treatise De Psalterio Manuscripto Capelliano ob singularem elegantiam commemorabili observatio, written by Johann Heinrich von Seelen (1687–1762) and published in the third volume of his Meditationes Exegeticae, quibus varia utriusque Testamenti loca expenduntur et illustrantur, Lübeck 1737. Von Seelen’s treatise is based on an autoptic study of the codex. He informs his readers that the codex once belonged to Rudolphus Capellus (1635–1684), professor of Greek and History at the Gymnasium Academicum in Hamburg. Von Seelen gives a detailed description of the codex, which leaves no doubt about its identity with the Psalter now in Copenhagen. He also states that the codex was sent to him for his use and information by his friend Michael Richey (1678–1761) in Hamburg. Michael Richey had been a colleague and close friend of Fabricius, who must have copied the codex while it was in Richey’s library. After Rudolphus Capellus’ death it passed on to his son Dietericus Matthias Capellus (1672–1720), who noted down the bibliographical notes on the sheet of paper attached to the codex. It was sold by auction as part of the bibliotheca Capelliana in Hamburg in 1721, and it will have been on that occasion that Michael Richey acquired it.   It is not known where and how Rudolphus Capellus acquired the Psalter. Von Seelen called it Capellianum, because Capellus was the first owner known to him. In the present paper the old Benedictine nunnery in Buxtehude, Altkloster, is suggested as the likely previous home of the codex. The short distance from Hamburg to Buxtehude, Capellus’ limited radius of action, and the fact that Altkloster was dissolved as a catholic monastery exactly in the period when Capellus acquired the codex is adduced in support of the hypothesis. In addition, archival material in Stade confirms that there were still several medieval manuscripts in the monastery when it was dissolved as a consequence of the Peace of Westphalia. Only one of them has been identified – actually another manuscript that found its way into the Thott collection in Copenhagen. This manuscript, Thott 8 8º with a late medieval German translation of the New Testament, contains a note in the hand of its first modern owner, Dietrich von Stade (1637–1718), which attests the presence of medieval books in Altkloster even as late as in 1696. They had been taken over by the first Lutheran minister in the former monastery and were in the custody of his widow when Dietrich von Stade visited it.   Capellus left his marks and scars on the manuscript. His hand, which I recognize from an autograph manuscript now in the Fabricius Collection, can be identified as the one that added numbers to the psalms. He also added the heading to the list of relics on top of f. 1r, and four lines of text on f. 199v. He added a note to the prayer on f. 16v, and even wrote down the Greek passages in the NT as parallels to the Latin canticles Magnificat and Nunc dimittis on f. 185r–185v.   As to the medieval additions in the manuscript it is pointed out in the paper that the owner of the relics listed on the first page of the book was not the owner of the manuscript. The name was erased at an unknown date, but the letters dns (for dominus) before the erasure indicate that the owner was a man, not a woman or a church or a monastery. It is suggested that the list of relics is probably younger than usually assumed. The text that Capellus completed with the four lines and a final Amen at the very end of the codex is itself an addition to the original manuscript. Despite its length (f. 194v–199v) it has received little attention from scholars. It is actually a version of the so-called Oratio Sancti Brandani, copied in a late medieval hand that imitates the script of the Psalter proper. Palaeographically as well as textually it appears to be a foreign element in the context of the Psalter, but it is, of course, interesting for its history. The text ends abruptly, so Capellus’ addition may perhaps be seen as more justifiable here than elsewhere in the book.   The only date explicitly noted down in the entire codex is found in the calendar. There are two medieval additions in it, one, little noticed, mentioning the 11.000 virgins in October, and the one noting the death of Eric duke of Jutland in year 1272, added to the line of the 27th day of the month of May. The present paper offers new suggestions as to how to understand the notices, and argues against the interpretation most often put forward, namely that Mechtilde was the direct or indirect authoress of the obituary-notice about duke Eric. It also argues against the identification of Mechtilde with the ego of the prayer on f. 16v. Based on palaeographical and other formal observations it is contended that the text should be dated to the end of the 13th Century and not its beginning, and that Byrgerus dux is likely to be the younger Birger Jarl, not the older. It is pointed out that he is not included in the prayer as a family member, but merely as Byrgerus dux. Following a structural analysis of the text, it is concluded that the anonymous voice of prayer is not that of Mechtilde; instead it is suggested that it could belong to an otherwise unknown daughter of Mechtilde and king Abel, and thus a sister of Eric duke of Jutland. Her place was a monastery, her present time the year 1288 or later.   Prayers beginning with words Suscipere digneris are found in many variations in medieval manuscripts. In one source, MS 78 a 8 in the Kupferstichkabinet in Berlin, a Psalter, this prayer as well as other significant elements, display a striking similarity with the Copenhagen Psalter. The Berlin Psalter, which is younger than the Copenhagen Psalter, has added elements that relates to persons in Sweden and Norway. The Berlin Psalter was presented to the nuns in Buxtehude in 1362 by a miles who passed by from his hometown in the western part of Northern Germany. The relation between the Psalters now in Berlin and Copenhagen is complicated. In the present paper it is suggested that, with respect to the prayer, they may depend on a common source. It is concluded that the Berlin Psalter may have had closer links to the Folkungar in Sweden than the Copenhagen Psalter, whose history, in so far as we know it, points rather to its presence in Medieval Jutland, that is Southern Denmark and Northern Germany.